Primary malignant mixed Müllerian tumors of the fallopian tube with cervix metastasis: A rare case report and literature review. Issue 28 (July 2018) - Zhang, QinHe; Liu, Ailian; Wu, Jing Jun; Niu, Miao; Zhao, Ying; Tian, Shi Feng; Chen, AnLiang; Zhong, Lin
Abstract: Rationale: Primary malignant mixed mullerian tumors of the fallopian tube is very rare and has only 1 case in the current literature with cervix metastasis. Patient concerns: We reported a 49-year-old woman sufferring from primary malignant mixed mullerian tumors of the fallopian tube with cervix metastasis, and the imaging examination found a strip of solid mass in the right fallopian tube and a nodular mass in cervical canal, which were both hyperintense on T2 weighted image (T2 WI) and diffusion weighted image (DWI) and continuous moderate enhancement on dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Diagnoses: The diagnosis was confirmed according to the specific anatomical location and pathological examination which was proved as primary malignant mixed mullerian tumors of the fallopian tube with cervix metastasis. Interventions: The patient underwent radical hysterctomy, bilateral adnexectomy, pelvic lymph node dissection, omentum majus excision and intravenous chemotherapy. Outcomes: Her posttreatment condition was good. Lessons: Primary malignant mixed mullerian tumors of the fallopian tube can be located by magnetic resonance image examination, which may also offer several diagnostic tips according to changes in signal and enhancement. When combined with pathological findings, qualitative diagnosis can be determined. Surgery and adjuvant chemotherapy are considered as effective methods. Our paper discussed its epidemiology, clinical symptoms, pathologic characters, therapeutic method as well as magnetic resonance imaging findings suggesting the diagnosis and differential diagnosis, including precontrast scan, contrast scan and diffusion weighted image and provided magnetic resonance imaging characteristics of primary malignant mixed mullerian tumors of the fallopian tube described in other literatures.